Determination of volatile compounds in fresh and fermented nipa sap (Nypa fruticans) using static headspace gas chromatography-mass spectrometry (GC-MS) - Radi, Nur Aimi; Abu Bakar, Fatimah; Mat Hashim, Dzulkifly (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Nipa sap or air nira is a sweet natural beverage obtained from a type of palm tree, Nypa fruticans. It is readily and spontaneously fermented resulting in the development of alcoholic fermentation products. Objective of this study is to determine the volatile compounds (VOCs) responsible for the aroma in fresh and fermented nipa sap. The sap was left for natural fermentation at 30°C for 63 days. VOCs of the sap were analysed using static headspace gas chromatography-mass spectrometry (GC-MS). Fresh nipa sap contained ethanol (83.43%), diacetyl (0.59%), and esters (15.97%). Fermented nipa sap contained alcohols (91.16-98.29%), esters (1.18-8.14%), acetoin (0.02-0.7%), diacetyl (0.04-0.06%), and acetic acid (0.13-0.68%). Concentration of ethanol in fresh nipa sap increased from 0.11% (v/v) to 6.63% (v/v) during the fermentation, and slightly decreased to 5.73% (v/v) at day 63. No higher alcohols were detected in the fresh nipa sap. Concentration of 1-propanol and 2-methylpropanol were constant throughout the fermentation with average of 0.004 to 0.006% (v/v) and 0.0001 to 0.0009% (v/v), respectively. 3-methylbutanol increased during the fermentation process. The highest concentration (0.001% v/v) was recorded at day 35. This study has shown differences in VOCs types between fresh and fermented nipa sap.